2003
DOI: 10.1016/j.chembiol.2003.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Immunization with Peptide-Functionalized Carbon Nanotubes Enhances Virus-Specific Neutralizing Antibody Responses

Abstract: Mole ´culaire et Cellulaire UPR 9021 CNRS functionalized carbon nanotubes with a remarkable solubility, particularly in water [8]. The organic modification Immunologie et Chimie The ´rapeutiques 15 Rue Rene ´Descartes of carbon nanotubes provides multiple sites for the attachment, through stable covalent bonds, of drugs, 67084 Strasbourg France amino acids, sugars, DNA, oligonucleotides, peptide nucleic acids (PNAs), peptides, proteins, or enzymes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
283
1
4

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 497 publications
(292 citation statements)
references
References 38 publications
(1 reference statement)
4
283
1
4
Order By: Relevance
“…If an antigen is linked to a CNT, the resulting construct could be more easily phagocytosed and rapidly introduced into the immune system, thus improving the antibody response. Pantarotto et al [53,54] demonstrated the potential of using CNTs for animal 90 immunization. In their seminal work, a peptide from the foot-and-mouth disease virus (FMDV) was covalently coupled to amino-derivatized single-walled carbon nanotubes (SWNTs), and this conjugate was administered to mice.…”
Section: Introductionmentioning
confidence: 99%
“…If an antigen is linked to a CNT, the resulting construct could be more easily phagocytosed and rapidly introduced into the immune system, thus improving the antibody response. Pantarotto et al [53,54] demonstrated the potential of using CNTs for animal 90 immunization. In their seminal work, a peptide from the foot-and-mouth disease virus (FMDV) was covalently coupled to amino-derivatized single-walled carbon nanotubes (SWNTs), and this conjugate was administered to mice.…”
Section: Introductionmentioning
confidence: 99%
“…Efforts have been made to assess cytotoxicity and to comprehensively enhance CNT biocompatibility. Cellular assays have been studied extensively using several cell types such as skin (HaCaT), lung (A549), pharynx (FaDu), blood-cell elements (macrophages), kidneys (HEK293) and disease-specific animal models such as human volunteers, rats, pigs, mice and rabbits [18][19][20][21][22][23][24][25][26][27][28][29]. Skin, lungs and blood-borne cells are relatively more challenging but are easily accessible organs in a given CNT-polluted environment [30].…”
Section: Introductionmentioning
confidence: 99%
“…Both methods demonstrated that the SWNTs-linked peptide retained the structural features required for recognition by anti-FMDV peptide monoclonal and polyclonal antibodies [148,211].…”
Section: Presentation and Immunogenic Potential Of Peptide Antigens Amentioning
confidence: 99%